Sharia-Compliant Crowdfunding Platforms as a Financial Innovation for Supporting Green Startups in Emerging Economies - Abdul Rahim; Trie Hierdawati; Elman Azizov (International Forum of Researchers and Lecturers, 2024)
This study explores the role of Sharia-compliant crowdfunding platforms as ethical financial innovations in supporting green startups, particularly in emerging economies. Green startups, which are inherently mission-driven and environmentally conscious, often face challenges in accessing traditional funding due to the long-term nature of their returns and perceived investment risks. Conventional financing mechanisms are frequently profit-oriented and risk-averse, making them unsuitable for ventures that prioritize sustainability and community impact. In contrast, Sharia-compliant crowdfunding platforms offer alternative financing pathways that are grounded in Islamic ethical principles, such as profit-and-loss sharing and the prohibition of interest and speculation. The research uses a qualitative-comparative case study approach, drawing from secondary data and interviews with platform operators and green startup founders. Thematic and comparative analyses reveal that Sharia crowdfunding platforms not only attract ethically motivated investors but also foster trust, transparency, and alignment with the values of environmentally conscious communities. These platforms provide higher levels of ethical accountability, although they are currently limited by low public literacy and a lack of regulatory frameworks in many regions. The study concludes that Sharia-compliant crowdfunding platforms have significant potential to bridge the financing gap for green startups. Their success depends on collaborative support from government, financial institutions, and academia, along with increased efforts in education and regulatory development. By integrating religious ethics and sustainable finance, these platforms can help create inclusive, transparent, and socially responsible funding ecosystems that contribute meaningfully to green economic growth.